2016
DOI: 10.1002/alr.21804
|View full text |Cite
|
Sign up to set email alerts
|

Failure pressures after repairs of 2-cm × 2.5-cm rhinologic dural defects in a porcine ex vivo model

Abstract: All glued repairs performed better than non-glued repairs. Both D/T and FL/T repairs performed better than B/T repairs. No repair tolerated pressures throughout the full range of adult supine intracranial pressure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 19 publications
1
7
0
Order By: Relevance
“…Consistent with our previous work, 18,19 the No Additional Support repair mean failure pressure of 6.494 ± 2.553 mm Hg demonstrated an inability to maintain a hermetic seal at the lower limits of normal physiologic ICP. Interestingly, the Direct Support repair with the FBC withstood an even lower average pressure of 5.103 ± 3.913 mm Hg, with a wider variation of tolerated pressures.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Consistent with our previous work, 18,19 the No Additional Support repair mean failure pressure of 6.494 ± 2.553 mm Hg demonstrated an inability to maintain a hermetic seal at the lower limits of normal physiologic ICP. Interestingly, the Direct Support repair with the FBC withstood an even lower average pressure of 5.103 ± 3.913 mm Hg, with a wider variation of tolerated pressures.…”
Section: Discussionsupporting
confidence: 89%
“…33 Despite these cohort studies, there have been no controlled studies that identify the effect of packing on the strength of skull base repairs. The authors’ previous work in an ex vivo model suggested that most unsupported repairs of small (5 mm) 18 and large (2.5 cm) 19 cranial base defects are unable to withstand elevated intracranial pressures; therefore, it is arguably beneficial to perform ancillary measures to acutely bolster the repair as it heals.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work reported that collagen matrix and fibrin glue performed better than nonglue repairs in an ex vivo model. 5…”
Section: Discussionmentioning
confidence: 99%
“…The test design was a modification of an apparatus used in a previous study. 5,7 The device was fabricated from 2 00 polyvinyl chloride (PVC) piping as depicted in Figure 1. A small hole was drilled on the side of the end cap, with a 3-way stop cock used to infuse saline solution and monitor chamber pressure, simulating increasing ICP.…”
Section: Testing Apparatusmentioning
confidence: 99%
See 1 more Smart Citation